Relevansi Pemikiran Ibn Sina Tentang Jiwa Bagi Kesehatan Mental Modern - Musliadi .; Nurlaelah Abbas; Usman Jafar (CV. ITTC INDONESIA, 2026)
Mental health issues are among the major challenges faced by modern society. Technological development, academic and occupational pressures, urbanization, and rapid lifestyle changes have increased the incidence of stress, anxiety, depression, and loss of meaning in life. Various scientific approaches in modern psychology and psychiatry have been developed to address these problems; however, moral and spiritual dimensions often receive insufficient attention. In this context, the ideas of classical Islamic philosophers, particularly Ibn Sina, provide important contributions to developing a more holistic understanding of the human person and mental health. This study aims to examine the relevance of Ibn Sina’s concept of the soul to modern mental health. The method used is library research through analysis of Ibn Sina’s works and contemporary psychological literature. Ibn Sina classifies the soul into vegetative, animal, and rational faculties, and emphasizes the balance between intellect, emotion, and human appetites. The results of this study indicate that Ibn Sina’s concept of psychic balance is highly relevant to modern mental health, especially in integrating rational, ethical, and spiritual aspects into the process of healing and maintaining psychological well-being.